2019
DOI: 10.1111/neup.12558
|View full text |Cite
|
Sign up to set email alerts
|

Altered immunoreactivity of ErbB4, a causative gene product for ALS19, in the spinal cord of patients with sporadic ALS

Abstract: ErbB4 is the protein implicated in familial amyotrophic lateral sclerosis (ALS), designated as ALS19. ErbB4 is a receptor tyrosine kinase activated by its ligands, neuregulins (NRG), and plays an essential role in the function and viability of motor neurons. Mutations in the ALS19 gene lead to the reduced autophosphorylation capacity of the ErbB4 protein upon stimulation with NRG‐1, suggesting that the disruption of the NRG–ErbB4 pathway causes motor neuron degeneration. We used immunohistochemistry to study E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…This pathway regulates cell proliferation, migration, differentiation, and apoptosis via MAPK, Akt, and related pathways. ErbB4 is also implicated in familial and sporadic ALS and altered in sporadic ALS spinal cord tissue (Takahashi et al, 2013(Takahashi et al, , 2019Dols-Icardo et al, 2018;Narain et al, 2019). ErbB tyrosine kinase receptors bind neuregulins, neurotrophic factors highly expressed in the CNS, which play a critical role in motor neuron function and survival (Mautino et al, 2004;Schram et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway regulates cell proliferation, migration, differentiation, and apoptosis via MAPK, Akt, and related pathways. ErbB4 is also implicated in familial and sporadic ALS and altered in sporadic ALS spinal cord tissue (Takahashi et al, 2013(Takahashi et al, , 2019Dols-Icardo et al, 2018;Narain et al, 2019). ErbB tyrosine kinase receptors bind neuregulins, neurotrophic factors highly expressed in the CNS, which play a critical role in motor neuron function and survival (Mautino et al, 2004;Schram et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A heterozygous mutation in ERBB4 (c.2136T>G, p.Ile712Met) was also reported in late-onset alS/FTD ( 18 ). Moreover, in the pathophysiology of ALS, immunofluorescence staining showed that ERBB4 immunoreactivity was decreased in the spinal cord of sALS patients, which further indicates that ERBB4 is involved in the pathophysiological process of sALS ( 19 ). In this study, we screened ERBB4 variants in a large cohort of ALS patients from mainland China to determine their pathogenicity and frequency.…”
Section: Introductionmentioning
confidence: 92%
“…An ectopic oligodendroglial ErBB4 immunoreactivity could also be detected. Interestingly, the expression of ErBB4 and TDP-43 appeared to be mutually exclusive in oligodendrocytes [ 106 ].…”
Section: Pathological Inclusions In Oligodendrocytes From Als Patimentioning
confidence: 99%